Role of Rab10 in cocaine-induced behavioral effects is associated with GABAB receptor membrane expression in the nucleus accumbens - Yu, Zhuoxuan; Fu, Qiang; Qiu, Tianyun; Yang, Caidi; Lu, Mingfen; Peng, Qinghua; Yang, Jianhua; Hu, Zhenzhen (Frontiers in Pharmacology, 2024)
Aim Previous studies have demonstrated that Ras-related GTP-binding protein Rab10 (Rab10) plays a role in psychostimulant-induced behavioral effects. In this study, we showed that Rab10 in the nucleus accumbens (NAc) of male animals affects the development of cocaine-induced behavioral effects, which are associated with the plasma membrane expression of the GABAB heteroreceptor (GABABR). Methods We performed flow cytometry, immunoendocytosis, pHluorin activity analysis, electrophysiology analysis, and open-field testing to explore the role of Rab10 in modulating the membrane expression and function of GABABR and its regulatory effect on cocaine-induced behavioral effects. Results Transcriptomics analysis showed that Rab10 was elevated following acute cocaine treatment. Membrane levels of Rab10 increased within day 1 of the cocaine treatment, subsequently decreasing at later time points. Rab10 deficiency in NAc regions significantly increased cocaine-inhibited membrane GABABR levels and inhibited cocaine-induced hyperlocomotion and behavioral sensitization. In addition, GAD67+-expressing neurons from NAc regions treated with cocaine revealed a significant decrease in Rab10 membrane expression. Furthermore, NAc neuron-specific Rab10 knockout resulted in a significant increase in the cocaine-inhibited membrane expression of GABABR, along with increased miniature inhibitory postsynaptic current (mIPSC) amplitude and attenuation of baclofen-amplified Ca2+ influx. Conclusion These results uncover a new mechanism in which Rab10-GABABR signaling may serve as a potential pathway for regulating cocaine-induced behavioral effects.